“The Song of Words” teaching multi-word units with songs - Tomczak, Ewa; Lew, Robert (Penerbit Universiti Kebangsaan Malaysia, 2019)
The need to integrate songs into English Language Teaching (ELT) has been recognized on numerous occasions. Song lyrics host multi-word units which learners can reuse as building blocks in their English, thereby reducing language processing time and effort, and improving their fluency as well as idiomaticity, thus bringing them closer to the native speaker norm. We report on two studies into the effectiveness of using songs for teaching multi-word units to high-school Polish learners of English. The same items were taught to two groups of EFL learners, but only one of the groups heard them in a song. Learners’ vocabulary recall was measured at three points in time relative to the teaching: before, immediately after, and a week after. The group taught with songs showed a significant recall advantage over the other group, especially when tested a week from teaching. The results suggest that songs can be an effective vehicle for teaching English multi-word units.